Facial Skin Smoothness as an Indicator of Perceived Trustworthiness and Related Traits. (April 2016) - Tsankova, Elena; Kappas, Arvid
Facial texture has typically been studied as an umbrella phenomenon comprising several properties, such as skin tone and smoothness. Furthermore, texture has normally been addressed within complex models including also structural and dynamic properties and focusing on the extraction of perceptual dimensions from large numbers of physical and personality traits. It is yet unclear how individual facial textural properties affect the perception of individual physical and personality traits. We took a step in this direction by showing that the manipulation of a single facial textural property (skin smoothness) affected explicit evaluations of trustworthiness, competence, attractiveness, and health independently and in combination. Within the context of skin smoothness, our data also suggest a direct perceptual route for physical and an indirect perceptual route for personality traits.